Genomic analysis of SARS-CoV-2 Circulating during Second and Third Wave of COVID-19 in Nepal - Tamrakar, Dipesh; Katuwal, Nishan; Adhikari, Navin; Madhup, Surendra Kumar; Dhimal, Meghnath; Shrestha, Rajeev (Journal of Nepal Health Research Council, 2023)
Background: In Nepal, since the first detection of COVID-19 case in January 2020, the total cases have rose to almost a million with more than 12,000 deaths. Till now, WHO has classified 5 variants of SARS-Cov2 as variant of concerns at different time points causing many waves in different countries and regions at different time points. Nepal had also faced three distinct waves of COVID-19 caused by different variant of COVID 19. The objective of this study was to perform whole-genome sequencing of SARS-CoV-2 circulating in different waves of COVID-19 in Nepal and investigate its variant or lineage.Methods: In this study, samples from 49 SARS-CoV-2 infected subjects from May 2021 to January 2022, were investigated. The methodology followed RNA extraction, real-time PCR for confirmation and whole-genome sequencing. The consensus genomes were interpreted with appropriate bioinformatics tools and databases.Results: Sequence analysis of 49 genomes revealed to be of Delta (n=27) and Omicron Variant (n=22). The mutations in the consensus genomes contained the defining mutations of the respective lineages/variants. There were 20 genomes of Omicron sub-lineage BA.2, 1 of BA.1.1 and 1 of B.1.1.529.Conclusions: This study provides concise genomic evidence of presence of Delta and Omicron variant of COVID-19 in Nepal. Delta and Omicron variants were driving the second wave and the third wave of COVID-19 respectively in Nepal. Therefore, the genomic surveillance must be increased to clearly map out the pandemic and strategize vaccination approaches in the country.Keywords: COVID-19; delta, omicron; Nepal;SARS-CoV-2; whole-genome sequencing